Autobiografia jako narzędzie badań historyka idei : casus Wspomnień niezależnego Richarda Pipesa - Citkowska-Kimla, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The aim of the article is to develop a research tool for a historian of ideas in the form of an autobiography. It is about framing when a personal document meets the criteria of being a tool for a historian of political thought. The conclusions included the thought that the memories must be meta-considerations on the subject of written autobiography or an analysis of the problem of auto-biography within the framework of the created philosophy or history vision. Examples representing this narrative type were left by, among others, Johann Gottfried Herder, Johann Wolfgang Goethe, Thomas Carlyle, Samuel Taylor Coleridge, Friedrich Nietzsche, Benedetto Croce, Robin G. Collingwood, and in Poland Stanisław Brzozowski. The volume of Richard Pipes’ memoirs, Memoirs of a Non-belonger, which is the foundation for the analysis, has also become part of the trend. The most important thinkers who have studied the issue of autobiography in depth include Wilhelm Dilthey and Georg Misch. The conclusions of the analysis are as follows: autobiography has a philosophical and epistemological meaning in the field of knowledge about human nature. In this sense, autobiography becomes part of anthropology, while anthropology is the foundation for the history of ideas, including political thought.
Keywords: autobiografia; Pipes, Richard; Paczkowska-Łagowska, Elżbieta; Dilthey, Wilhelm; Misch, Georg